Advances in Nanotheranostic Systems for Concurrent Cancer Imaging and Therapy: An Overview of the Last 5 Years - Anna Małgorzata Lankoff; Malwina Czerwińska; Marcin Kruszewski (Molecules)
The rapid development of nanotechnology during the last two decades has created new opportunities to design and generate more advanced nanotheranostics with diversified capabilities for diagnosis, drug delivery, and treatment response monitoring in a single platform. To date, several approaches have been employed in order to develop nanotheranostics. The purpose of this review is to briefly discuss the key components of nanotheranostic systems, to present the conventional and upcoming imaging and therapeutic modalities that employ nanotheranostic systems, and to evaluate recent progress in the field of cancer nanotheranostic systems in the past five years (2020–2024). Special attention is focused on the design of cancer nanotheranostic systems, their composition, specificity, potential for multimodal imaging and therapy, and in vitro and in vivo characterization.